2016
DOI: 10.1016/j.jprocont.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate batch to batch optimisation of fermentation processes incorporating validity constraints

Abstract: This paper presents an innovative optimisation technique, which utilises an adaptive Multiway Partial Least Squares (MPLS) model to track the dynamics of a batch process from one batch to the next. Utilising this model, an optimisation algorithm solves a quadratic cost function that identifies operating conditions for the subsequent batch that should increase yield. Hard constraints are shown to be required when solving the cost function to ensure that batch conditions do not vary too greatly from one batch to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The synthesis process of cobalt oxalate is a typical batch production process. The liquid phase reaction equation between ammonium oxalate and cobalt chloride in solution is as follows [ 35 ] : CoCl2+()NH42normalC2normalO4CoC2normalO4+2NH4Cl …”
Section: Simulation Research and Results Analysismentioning
confidence: 99%
“…The synthesis process of cobalt oxalate is a typical batch production process. The liquid phase reaction equation between ammonium oxalate and cobalt chloride in solution is as follows [ 35 ] : CoCl2+()NH42normalC2normalO4CoC2normalO4+2NH4Cl …”
Section: Simulation Research and Results Analysismentioning
confidence: 99%
“…The batch to batch optimization strategy was then benchmarked with a fed-batch fermentation simulation of S. cerevisiae . The authors reported an almost 5-fold increase of biomass yield in <20 batches [87] . In 2020 the same authors applied their previously developed multivariate statistical process model to “a realistic industrial-scale fed-batch penicillin simulator” for batch to batch optimization of penicillin yield by adjusting the glucose feed rate [88] .…”
Section: Modeling In Process Controlmentioning
confidence: 96%